A comparison of intensive vs. light-touch quality improvement interventions for maternal health in Uttar Pradesh, India - Dominic Montagu; Katie Giessler; Michelle Kao Nakphong; Cathy Green; Kali Prosad Roy; Ananta Basudev Sahu; Kovid Sharma; May Sudhinarset (BMC, 2020)
Abstract Background Poor patient experiences during delivery leads to delayed presentation at facilities and contributes to poor maternal health outcomes. Person-centered maternity care (PCMC) is a key component of quality. Improving PCMC requires changing the process of care which can be complex and necessitate significant external input, making replication and scale difficult. This study compares the effectiveness two Quality Improvement (QI) intervention phases, one Intensive, one Light-Touch. Methods We use a matched case-control design to compare two phases of a QI Intervention targeting PCMC, with three facilities in each. The Intensive phase was introduced into three government facilities where teams were supported to identify, design, and test potential improvements over 12 months. The Light-Touch phase was subsequently introduced in three other government facilities and changes were tracked over six months. We compared the two groups using multivariate linear regression and difference-in-difference models to assess changes in PCMC outcome Results Both Intensive and Light-Touch arms demonstrated large improvements in PCMC. On a scale from 0 to 100, Intensive facilities increased in PCMC scores from 85.02 to 97.13, while Light-Touch facilities increased from 63.42 to 87.47. For both there was a 'halo' effect, with a similar improvement recorded for the specific improvement activities focused on, as w ell as aspects of PCMC not directly addressed. Conclusions This study demonstrates that a short, inexpensive, light-touch and directive intervention can change staff practices and significantly improve the experiences of women during childbirth. It also shows that improvements in a few areas of provider-patient interaction have a 'halo' effect, changing many other aspects of patient-provider interaction at the same time. Trial registration QI Phase 1 - NCT04208867 . Retrospectively registered. December 19th, 2019. QI Phase 2 - NCT04208841 . Retrospectively registered. December 23, 2019.